Global Culture of Cybersecurity: A Multi-vocal Literature Review Protocol - Muahammad, Nisar; Khan, Siffat Ullah (The Lighthouse Journal of Social Sciences, 2024)
With the increasing use of technology and interconnected devices globally, the number of cyber-attacks has also grown exponentially. Technological countermeasures alone are insufficient to effectively control these attacks at an acceptable level. Despite advancements in technology, human errors and vulnerabilities continue to pose significant challenges in protecting digital assets worldwide. One of the most effective methods to mitigate cyber-attacks is to establish and nurture a culture of cybersecurity at the global, national, organizational, and group levels. While much research has been focused on organizational and national-level cybersecurity culture, the research pertaining to global cybersecurity culture is currently lacking and underexplored. This gap is evident in the limited academic literature addressing global cybersecurity culture. However, there is grey literature available from various regional and international organizations and cybersecurity forums, such as policy documents, reports, and white papers that provide valuable insights and practical perspectives. The primary objective of this research is to develop a protocol for conducting a comprehensive literature review to evaluate existing literature, both white and grey, and highlight advancements in the field of global cybersecurity culture and propose future directions. We are currently implementing this protocol.